The effectiveness of Go Green implementation among society in Kota Bharu, Kelantan - Che Rusuli M. S.; Naqiah M.; Fitriani Q; Syahida N.; Hakim M. (European Center for Science Education and Research, 2016)
Nowadays, Go Green has becoming an initiative in protecting the natural resources for the next generation and protects human health through environmental management and implementation of green ways of life. This study seeks to identify the effectiveness of the implementation of Go Green by Majlis Perbandaran Kota Bharu (MPKB) Kelantan. The population of this study includes society in Kelantan and 200 respondents will be involved which is lives in Pengkalan Chepa, Kubang Kerian, Pasir Tumboh, Wakaf Bharu and Kijang. The results from this study hoped will contribute to the body of knowledge which has a positive significant relationship with education, technologies and legal actions.